DO THEORIES OF CONSCIOUSNESS REST ON A MISTAKE? - Pautz, Adam (Philosophical Issues, 2010)
The article offers the author's insights regarding the dependence of the standard theories of consciousness on mistake. The author says that the standards theories of consciousness had adopted reductionism, and rejected the reductive explanation being referred as primitivism. Moreover, he discusses the two parts of tracking intentionalism under the standard theories of consciousness which are the response-independent reductionism and the tracking theory.